Promoting shared decision-making in colorectal cancer screening in primary care: A cluster randomized controlled trial - Tamara Scharf; Yonas Martin; Marc-Andrea Janggen; Adrian Rohrbasser; Kali Tal; Nikola Biller-Andorno; Jean-Luc Bulliard; Kevin Selby; Reto Auer (PLoS ONE, 2026)
Introduction In Switzerland, primary care physicians (PCP) prescribe colonoscopy for colorectal cancer (CRC) screening rather than offering a choice between colonoscopy and faecal occult blood test (FOBT). This study evaluated a training program promoting shared decision-making for CRC screening. Methods PCP from a research network were randomized 1:1 into intervention or control. The intervention group received study materials, patient decision aids, evidence summary, FOBT sample kit, and personalized feedback on CRC screening practices. PCP documented CRC screening decisions of 40 consecutive patients (ages 50–75) four months post-intervention. The control group received no materials before data collection. Results Of 110 PCP randomized, 83 (76%) collected data on 3,171 patients (mean age 62, 50% women). PCP in the intervention group were more likely than controls to have at least one patient tested or planning FOBT (84% vs. 56%; unadjusted RR: 1.52; 95% CI: 1.13 to 2.04). In a sensitivity analysis restricted to 62 PCP who participated in a previous data collection, 72% (21/29) already met the primary outcome in the intervention group at baseline and 49% (16/33) in the control group (RR: 1.49; 95% CI: 0.98 to 2.28). When contrasting the change within PCP from the 2017 and 2018 data collection, there was no significant increase in proportion of PCP who met primary outcome between intervention and control group, while it might have increased the proportion of PCP already prescribing FOBT to prescribe it to more of their patients. Conclusion A mailed intervention increased FOBT prescriptions, but selection bias may have influenced results.